ANALISIS PEMAHAMAN KONSEPTUAL SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA MATERI SPLDV DITINJAU DARI GAYA BELAJAR - Rindang Diana Putri; Yuyu Yuhana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to observe students' ability to understand the concept of SPLDV and solve SPLDV problems, as well as to describe the conceptual understanding ability of class X students at SMK Negeri 9 Tangerang City on SPLDV material seen from learning styles. This research is a type of qualitative descriptive research. The data collection technique used in this research is a mathematical concept understanding test with 3 items of SPLDV material and interviews. The subjects in this study were 6 students of pharmacy X 1 SMK Negeri 9 Tangerang City. Data analysis techniques used include data reduction, data presentation, and drawing conclusions. The results of the study stated that students with visual learning styles were able to fulfill all indicators of concept understanding, while students with auditory and kinesthetic learning styles were sufficient in understanding the SPLDV concept, but in implementing the concepts and problem solving algorithms were still not good.